EVALUATION OF PHYTOCHEMICALS IN CERTAIN INDIAN SPICES FOR QUORUM SENSING INACTIVATION IN A PLANT PATHOGENIC BACTERIA - Y. APARNA; K. SAILENDRA; J. SARADA (The Bioscan, 2010)
Quorum sensing is a mechanism where bacteria produce and release chemical signals in search of similar cells in their close surroundings. Quorum sensing (QS) is a key regulator of virulence factor expression which includes protease, pyoverdin pyocyanin etc in Pseudomonas sps. Present study was made to evaluate effect of aqueous extracts of six Indian spices Allium sativum, Trigonella foenum, Trachyspermum amoni, Brassica junceae, Syzygium aromaticum and Piper nigrum for their antiquorum sensing activity against Pseudomonas sps. a lab isolate. Of all the six spices tested Allium sativum, Piper nigrum and Syzygium aromaticum showed significant inhibition in quorum sensing activity with less effect on bacterial growth. Our findings suggest that the quorum quenching mechanisms are not related to bacteriostatic or cidal effects.